2011
DOI: 10.3937/kampomed.62.29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kampo Therapy for Inpatient on Medical Economics

Abstract: We investigated prescriptions and drug costs at admission and discharge for 35 patients hospitalized in Department of Japanese Oriental (Kampo) Medicine, Chiba University Hospital from September 2006 to October 2008. They recovered after Kampo therapy from various non-acute diseases. The number of western drugs decreased from 3.7 at admission to 2.7 at discharge, thus their drug costs per day significantly decreased from 302.1 yen to 227.6 yen. The cost of Kampo medicines themselves, on the other hand, did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been reported that therapeutic regimens using Kampo medicines reduce the drug cost for patients compared with therapy using modern medicines [ 20 22 ]. Therefore, the relatively low cost of Kampo prescriptions is expected to have a considerable positive economic impact on cancer therapy, which frequently involves the use of expensive patented medicines.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that therapeutic regimens using Kampo medicines reduce the drug cost for patients compared with therapy using modern medicines [ 20 22 ]. Therefore, the relatively low cost of Kampo prescriptions is expected to have a considerable positive economic impact on cancer therapy, which frequently involves the use of expensive patented medicines.…”
Section: Resultsmentioning
confidence: 99%